A Systematic Indoor and Outdoor Study of the Effect of Particle Size and Concentration of TiO2 in Improving Solar Absorption for Solar Still Application - Samneang, Heng; Kumar, Laveet; Zafar, Amad; Ali, Muhammad Umair; Zahid, Taiba; Bibi, Saira; Ahmad, Muhammad Shakeel; Ghafoor, Usman; Selvaraj, Jeyraj (Frontiers in Materials, 2021)
Solar light absorber surface is probably one of the most important components in solar still that dictates the distillate yield. In this work, a systematic study is conducted to investigate the effect of particle size and concentration of titanium oxide (TiO2) in black paint in increasing the solar still absorber surface temperature. The various available particle sizes, i.e., 20, 150, and 400 nm, are mixed in black paint with varying concentrations and are applied on the absorber plate. XRD is used for phase identification of as-received powders. UV-Vis spectroscopy is used to examine light absorption properties. Finally, extensive indoor testing (using an improvised solar simulator) and outdoor testing are conducted to optimize the concentration. An increase in surface temperature is observed with the introduction of TiO2 nanoparticles in black paint. Furthermore, the increase in particle size leads to an increase in temperature. The highest surface temperatures of 104.86°C, 105.42°C, and 106.32°C are recorded for specimens with particles sizes 20 nm (at 15 wt% concentration), 150 nm (at 10 wt% concentration), and 400 nm (at 7 wt% concentration), respectively. Furthermore, the highest temperature of 69.69°C is recorded for TiO2-400 nm specimens under outdoor conditions, which is 15.97% higher than that of the bare aluminum plate. The increase in surface temperature may be due to high UV absorption. Moreover, an increase in particle size leads to high light-scattering ability, further improving the light-harvesting ability.